Reflexiones sobre la primera globalización ibérica - Marina Alfonso Mola (Mélanges de la Casa de Velázquez, 2018)
The presentation of several original papers about the action of the united Crowns of Spain and Portugal on some overseas territories (especially in Africa, Ceylon, Asian Far East and Persian Gulf) allows us to enlarge our reflection about the questions regarding what we can call the Iberian contribution to the first globalization.